The Main Needs of the Christian Family in the Contemporary Western Society - GOVOR, Marius Vasile (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2017)
The current article aims to draw our attention to the fact that the Christian modern family from western countries is experiencing turning points, and these events bring their consequences not on the family only, but on the society as well. Family and society influence reciprocally, and within the current social and political framework, family has the power to do something to get rid of this crisis in which it has entered since the confusion between the symptoms of its decay and its authentic needs. Therefore, the power hunger, strong desire for welfare, redefinition of the family concept, child protection services and other similar issues represent the grievous side of the contemporary society and prove once again that the real needs of the family are from the spiritual zone among the most important ones are: faith in God, obeying and fulfilling the Bible, being involved in a local church’s life, understanding the marriage covenant, spiritual guidance, prayer and genuine worship before God. As soon as the family has a clear understanding of its real needs, it will be able to find fulfillment and happiness it deserves and dreams of, and society will be revitalized and consolidated by these families.